Efficacy of first-line treatment with epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) alone or in combination with chemotherapy for advanced non-small cell lung cancer (NSCLC) with low-abundance mutation. (February 2019) - Yan, Xiangtao; Wang, Huijuan; Li, Peng; Zhang, Guowei; Zhang, Mina; Yang, Jinpo; Zhang, Xiaojuan; Zheng, Xuanxuan; Ma, Zhiyong
Highlights: Retrospectively identified patients with low-abundance EGFR mutations. EGFR-TKI combined with chemotherapy is better than TKI alone. EGFR-TKI combined with chemotherapy was well tolerated. Abstract: Objective: The objective of this study was to investigate whether first-line treatment with epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) in combination with chemotherapy improves the prognosis of patients with advanced non-small cell lung cancer (NSCLC) who harbour low-abundance EGFR mutations. Patients and methods: We retrospectively analysed the clinical data of 76 patients with advanced NSCLC who harboured low-abundance EGFR mutations. The patients were divided into the combination group and the monotherapy group. The combination group received EGFR-TKI combined with a platinum-based regimen. After the end of chemotherapy, EGFR-TKI was administered daily. The monotherapy group was administered EGFR-TKI therapy daily. Results: No significant difference was observed in response rate between the different groups. The median PFS and OS were significantly longer in the combination group than in the monotherapy group (PFS: 7.9 months [95% CI, 5.73–10.07] vs 5.9 months [95% CI, 4.99–6.81], p = 0.015; OS: 25.8 months[95% CI, 16.27–35.33] vs 19.8 months [95% CI, 18.60–21.00], p = 0.047). Subgroup analysis showed that, for patients with the exon 21 L858R mutation, the PFS and OS were significantly longer in the combination group than in the monotherapy group (PFS: 7.2 months vs 5.8 months, p = 0.013; OS: 22.0 months vs 18.7 months, p = 0.024). The incidence of adverse events was significantly higher in the combination group. Conclusion: For patients with advanced NSCLC and low-abundance EGFR mutations, first-line treatment with EGFR-TKI plus chemotherapy significantly improved PFS and OS. The combination therapy increased the incidence of adverse reactions, but all adverse reactions were expected and tolerated.